Some Built Environment Research Contributing to Sustainability - Wijeyesekera, Devapriya Chitral (International Journal of Integrated Engineering, 2013)
Engineering in all forms must address global challenges of sustainability including its dimensions such as poverty, urbanisation, and climate change. The built environment is the dynamic interface between human society as it interacts and influences the ecosystem. An understanding of this inextricably linked interdependence underpins the sustainability issues relevant to Civil Engineering. Geotechnical engineering outstand the rest of the disciplines in being the most resource intensive and having an early stance in the construction process. Philosophies and definitions of sustainability, as appropriate to geotechnical engineering is punctuated with illustrations through such research studies that contribute to sustainable development. This paper is thus a technical narrative of such innovative geotechnical research focusing on the author’s research career to include the modeling and assessment of the performance of a rectangular hyperbolic paraboloid shell foundation to mimic the “duck’s foot” on very soft mud; innovative research on the development of rocker pipes to arrest the often unnoticed failure of utility services arising from differential settlement; industrial design and sustainable installation of thick compacted London clay surround to protect the Heathrow Express Rail link Tunnel from noxious gases entering the tunnel as it traversed through an old landfill site; Urban Heat Island studies; Hemp in rammed earth construction,; Quality control and enhancement of geo synthetic clay liners; adoption of lightweight manufactured aggregates; used vegetable oil in asphalt pavements and soil stabilization and sustainable construction through use of enzymes and light geo composites on challenging soils are presented.